Mendorong usaha tani berkelanjutan melalui kolaborasi edukasi pupuk organik di Sukodadi - Shoimah, Siti; Sholikin, Ahmad; Trivena, Shinta Maharani; Himma, Faiqotul; Putri, Windy Anissa Amilia (Penamas: Journal of Community Service, 2025)
The agricultural sector in Sukodadi District, Lamongan, faces various structural challenges, including land degradation, dependency on chemical fertilizers, and fluctuations in climate and prices that impact the sustainability of farming activities. In response to these issues, a community engagement program was conducted through socialization and training on the use of petroganic organic fertilizers, in collaboration with CV Berkah Jaya as the strategic fertilizer distributor partner. This activity aimed to enhance farmers’ technical knowledge, environmental awareness, and managerial skills to promote sustainable agricultural practices. A participatory and contextual approach was used to ensure that the materials were easily understood and relevant to the farmers’ conditions. Post-activity survey results showed a significant increase in understanding (92%), recognition of environmental benefits (96%), and willingness to adopt organic fertilizers (87%). The program also broadened farmers’ perspectives on value-added potential and market access for organic agricultural products. These findings indicate that integrated education supported by cross-sector collaboration can drive behavioral change and strengthen agricultural resilience while contributing to the achievement of the Sustainable Development Goals (SDGs).